Application of information-based closed-loop management in optimizing surgical process (基于信息化的闭环管理优化手术流程的设计与实践) - ZHOU Liheng (周立恒); ZHU Xiaodong (朱小东); CHEN Qiannan (陈倩楠); LI Amin (李阿敏) (中西医结合护理)
To improve the information level of closed-loop surgical workflow by using personal digital assistance (PDA), and to realize reasonable, scientific, comprehensive and efficient closed-loop management of the whole surgical process. Based on the actual flow of operation, information technology was used as the basis. Medical staff operates the PDA to perform corresponding operations on patients who need surgery, and the information system captures the execution node (node set through the actual business content), the execution time and the integrated analysis of these data information to form a closed-loop style. A surgical closed loop suitable for hospital was constructed by means of information technology. The closed-loop of the whole surgical process based on PDA can optimize and standardize the surgical process, effectively extend the preoperative, intraoperative and postoperative medical services for patients, and has important significance for the fine management of surgery and the overall monitoring and management of hospitals. (利用个人数字助理(PDA)提升手术闭环工作流程信息化水平, 实现合理、科学、全面、高效的手术全流程的闭环管理。基于手术业务实际流转情况, 以信息技术为依托, 医护工作人员操作PDA对需手术的患者执行相应操作, 信息系统抓取PDA上执行节点(通过实际业务内容进行设置的节点)、执行人和执行时间, 并将这些数据信息集成分析形成闭环样式。通过信息化手段构建了适合医院的手术闭环, 实现了全流程数字化闭环管理。基于PDA的手术全流程闭环, 优化和规范了手术流程, 有效延伸了患者术前、术中和术后医疗服务, 对手术精细化管理、医院全面监控及管理均有重要意义。)